2013
DOI: 10.4236/ojic.2013.34011
|View full text |Cite
|
Sign up to set email alerts
|

Reaction in situ found in the synthesis of a series of lanthanide sulfate complexes and investigation on their structure, spectra and catalytic activity

Abstract: A series of lanthanide sulfates coordination complexes, Ln 2 (SO 4 ) 3 (H 2 O) 8 (Ln = Pr (1), Nd (2), Tb (3), Sm (4), Dy (5), Gd (7), Ho (8)), and EuK(SO 4 ) 2 (6), were constructed by the reaction in situ of lanthanide ions (Ln 3+ ) with flexible dodecanedioic acid and rigid aromatic 5-sulfosalicylic acid under hydrothermal conditions. All of them were characterized by elemental analysis, IR spectroscopy, and single-crystal X-ray diffraction. The crystal structures and coordination modes of metal centers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…The peak observed at 480 nm in the visible region indicates the band edge emission which is clear from the UV-visible absorption spectra of the present samples. The two peaks at 595 and 645 nm correspond to the characteristic ions present in the complex respectively [26]. The PL spectra of the pure neodymium β-diketonate complex at excitation wavelengths of 300, 400, 500 and 520 nm are shown in figure 12c.…”
Section: Pl Studiesmentioning
confidence: 99%
“…The peak observed at 480 nm in the visible region indicates the band edge emission which is clear from the UV-visible absorption spectra of the present samples. The two peaks at 595 and 645 nm correspond to the characteristic ions present in the complex respectively [26]. The PL spectra of the pure neodymium β-diketonate complex at excitation wavelengths of 300, 400, 500 and 520 nm are shown in figure 12c.…”
Section: Pl Studiesmentioning
confidence: 99%
“…Photoluminescence (PL) spectra of pure PMMA, surface-roughened PMMA, coaxial hollow PMMA nanofibres and the nanofibres with the samarium β-diketonate complex incorporated are shown in Figure 11. The PL spectra of the PMMA nanofibres of different architectures with the complexes incorporated were entirely different from that of the pure samarium complex [34,35] and matched well that of PMMA, which showed the successful incorporation of the complex into the fibre. Here it was observed that pure PMMA nanofibres showed maximum intensity at 330 nm with 501 148 cps.…”
Section: Photoluminescence Analysismentioning
confidence: 79%
“…Here the samarium complexes produced peaks at 598 nm and 644 nm, which represented the emissions from 4 G 5/2 to 6 H 7/2 and to 6 H 9/2 of interstitial Sm 3+ ions present in the complex; this finding was in agreement with many recent reports. [24,34,[36][37][38][39][40] PL analyses, therefore, clearly confirmed the successful incorporation of the complex into the pure and structurally modified PMMA nanofibres. Other peaks present in the spectra of pure, surface-roughened, and coaxial hollow PMMA nanofibres with the samarium complex incorporated originated from, for example, intermediate energy levels, donor-acceptor pair transitions, oxygen vacancies, and interstitial ions present in the prepared complexes.…”
Section: Photoluminescence Analysismentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, the FT-IR results reveal the formation of La 2 O 2 SO 4 after calcination of the precursor (La(III) complex).The bands at 631 and 591 cm −1 are attributed to the stretching vibrations of the La-O bonds[56,57]. The vibration bands at 1160, 1063, and 672 cm −1 can be due to the characteristic vibrations for the sulfate group[58][59][60].…”
mentioning
confidence: 99%